The role of government in the development of military science in Ukraine - Orlov, М. М. (Honor and Law, 2019)
The role of government military science in some countries of the world and in particular in Ukraine. The drawbacks of the use of scientific works in the military sphere, in practice, that can be remedied through government mechanisms. As one of the mechanisms proposed the concept of control subjects of public administration training highly qualified scientific personnel in the field of military sciences.